Impact of the subject and the distribution of training on memory - Omar, Abdel Khaleq El-Aswad; Nik Mohd Rahimi Nik Yusoff, (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2012)
Memory is responsible to improve the learner in the educational ladder, where the success of learning process is measured by the ability of the student to retrieve a set of information obtained during the period of time. It also refers to the continuation of memorizing the information that obtained by the learner. The type of training obtained by students in the classroom varies from teacher to another, some of them prefer to use related training and some of them prefer to use the separate training. As well as the type subject determines the type of training that we use. The aim of this study was to investigate the differences caused by the use of separate training for the collection of students in Arabic and mathematics subjects and to investigate the differences between the students gender for using the memory. The sample of this study consisted of 52elementary students of fifth level, in Badr City in Libya. The study focused on the use of the memory test for the numbers and words meaningless. The most important finding of the study was that there is no statistical difference between the pre-testing and pos-testing from statistical prospective for the numbers memory test. While the words memory test showed statistical differences between the tests and in the favor of the pre-testing. The study also found a non-statistically significant difference between the genders for using both testing memory tests for the females.